The interface of politeness strategies and power relations in disagreements among Egyptian students - Bakry, Hend Tarek (AUC Knowledge Fountain, 2015)
Disagreement is generally done in opposition to a speaker's claim, in an educational context it can be defined as a student's verbal or non-verbal opposition to classmates' or the teacher's stance that emerge through different instructional and non-instructional situations. The purpose of the study is to qualitatively examine Egyptian undergraduates' disagreements with participants of different power relations in EFL classrooms from a politeness theory perspective. The study introduces Egyptian EFL classrooms as a new context for studying the interface of power and politeness in disagreements in general and for exploring the impact of other variables such as context, social distance and type of interactional activities on the realization of disagreements. Data were collected through videotaping two classes of business-English, with a total of 18 hours of observation. In addition, interviews were conducted with a sub-set of the participants to gather in-depth information about the students’ pragmatic choices and a questionnaire evaluating social distance between peers was administered to all participants. In the 18 hours of data collected, 34 students expressed 90 turns of disagreement; 35 of these were directed to the teacher, while 55 were to peers. Spontaneous disagreements were coded and categorized according to the Brown and Levinson (1987) politeness theory using Rees-Miller’s (2000) taxonomy, adapted here to include strategies from Muntigl and Turnbull's (1998) taxonomy. Analysis of the data showed that although students employed various positive and negative politeness strategies to soften disagreements when addressing power superiors, students employed many aggravated disagreements when discussing the teachers' language input .The use of different negative politeness strategies and aggravated disagreements between peers were attributed to social distance and the type of interactional activities. The findings of this study might help provide some insight into the aspects that should be incorporated into the teaching of pragmatics in EFL classrooms.